2020
DOI: 10.1038/s41385-020-0287-5
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and pandemic influenza: 100 years of progress, still much to learn

Abstract: Influenza viruses are highly transmissible, both within and between host species. The severity of the disease they cause is highly variable, from the mild and inapparent through to the devastating and fatal. The unpredictability of epidemic and pandemic outbreaks is accompanied but the predictability of seasonal disease in wide areas of the Globe, providing an inexorable toll on human health and survival. Although there have been great improvements in understanding influenza viruses and the disease that they c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
66
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 87 publications
0
66
0
2
Order By: Relevance
“…Coinfections contribute significantly to morbidity and mortality in influenza. 1 Early data from China suggested co-infection in as many as 50% of deceased SARS-CoV-2 patients, 10 while other reports in milder disease suggest co-infection in 10% or less. Details on pathogens associated with co-infection are limited, but Chen et al described complex infections with a combination of Gram-negative pathogens identified, as well as fungi in a few cases.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Coinfections contribute significantly to morbidity and mortality in influenza. 1 Early data from China suggested co-infection in as many as 50% of deceased SARS-CoV-2 patients, 10 while other reports in milder disease suggest co-infection in 10% or less. Details on pathogens associated with co-infection are limited, but Chen et al described complex infections with a combination of Gram-negative pathogens identified, as well as fungi in a few cases.…”
mentioning
confidence: 99%
“…Dunning et al provide a comprehensive overview of current knowledge regarding seasonal influenza, with a detailed description on how the immunology of influenza has shaped the current standard of therapy and prevention. 1 This review was written in the period before the world was confronted with the SARS-CoV-2 outbreak, which for many might feel a long time ago, though in reality is only 2-3 months in the past. We now live in a very different world where a novel virus has redefined how we experience essential elements of modern life ranging from work and education to travel and recreation.…”
mentioning
confidence: 99%
See 3 more Smart Citations